2010
DOI: 10.1097/coc.0b013e31819cccc3
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Patterns of In-Breast Failure in Patients With Early Stage Breast Cancer Treated With Breast-Conserving Therapy

Abstract: This analysis demonstrates the inaccuracy of clinically establishing the clonality of most IBTRs. Clonally related IBTRs occurred sooner than clonally different IBTRs, were more frequently associated with the development of distant metastases and had a worse prognosis. Molecular clonality assays provide a reliable means of identifying patients who may benefit from aggressive systemic therapy at the time of IBTR and provide an accurate assessment of the efficacy of various forms of local therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 37 publications
1
5
0
Order By: Relevance
“…This confirms data showing that HG is a valuable prognostic factor [22], [32], [51], particularly in early breast cancer without lymph node involvement [10].…”
Section: Discussionsupporting
confidence: 90%
“…This confirms data showing that HG is a valuable prognostic factor [22], [32], [51], particularly in early breast cancer without lymph node involvement [10].…”
Section: Discussionsupporting
confidence: 90%
“…However, as the current study was retrospective, further evaluation may be required. The present study also included a mixture of patient tissue samples consisting of ‘true IBTR’ and ‘new primary tumors’; new primary tumors are not expected to have any correlation with the first primary tumor (1921). The timing of diagnosis of IBTR was distinct from that of the diagnosis following NAC.…”
Section: Discussionmentioning
confidence: 99%
“…Prior pathologic studies have shown the difficulty in correlating a clinical classification of a true recurrence relative to a molecular assessment of the clonality of initial and recurrent tumors(18). The recurrent tumors in our trial had the same receptor staining and similar morphology as the initial tumors, yet none of them recurred within 3 cm of the initial tumor site.…”
Section: Discussionmentioning
confidence: 99%